Answer:
a-2+3= -2

⇒ a+ (-2+3)= -2 (combine like terms)

⇒ a+ 1= -2

⇒ a= -2-1

⇒ a= -3

**Final answer: a=-3**~

⇒ a+ (-2+3)= -2 (combine like terms)

⇒ a+ 1= -2

⇒ a= -2-1

⇒ a= -3

Rationalize the denominator and simplify-

Danielle bought a new diary for $12.80. She paid with a $20 bill. How much change did she get back? A. $32.80 B. $8.20 C. $7.20 D. $7.10

What is -2/5 X -1 1/4 a: 1-1/10b: -1/2 c: 1 1/10d: 1/2

The table and the graph each show a different relationship between the same two variables, x and y:How much more would the value of y be in the table than its value on the graph when x = 11?100165395440

What is .03 as a percent and degree?

Danielle bought a new diary for $12.80. She paid with a $20 bill. How much change did she get back? A. $32.80 B. $8.20 C. $7.20 D. $7.10

What is -2/5 X -1 1/4 a: 1-1/10b: -1/2 c: 1 1/10d: 1/2

The table and the graph each show a different relationship between the same two variables, x and y:How much more would the value of y be in the table than its value on the graph when x = 11?100165395440

What is .03 as a percent and degree?

Area of a triangle = ½ * base * height

Area of blue triangle = ½ * 4 * 4

Area of blue triangle = 8

Area of red triangle = ½ * 4 * 3

Area of red triangle = 6

TOTAL AREA = 8 + 6 = 14

**Answer:**

-1

**Step-by-step explanation:**

Because 8-9=-1

If each** journa**l weighs about 280 grams what will be the **total weight **of three journals is:** 840 grams**

Using this **formula**

Total weight=Number of journal × Weight of each journal

**Where:**

Number of journal=**3**

Weight of each journal=**280 grams**

Let plug in the formula

Total weight=3×280 grams

Total weight=**840 grams**

Inconclusion if each** journa**l weighs about 280 grams what will be the **total weight **of three journals is: **840 grams**

Learn more here:

Well, to start this off- you have three journals. Each one weighs 380 grams. To solve this you have to multiply the weight of each journal with the amount of journals you have. And your answer should be 840

7 7/8 - 3 9/16

**Answer:**

4 5/16

**Step-by-step explanation:**

7 7/8 - 3 9/16

7 14/16 - 3 9/16

4 5/16

**Answer:**

7.1875

**Step-by-step explanation:**

778−3916

=778−3916

=778+−3916

=15416+−3916

=154+−3916

=11516(Decimal: 7.1875)

We need to just plug in n = 9 into the rule to find out the 9th term.

A(9)= -14+(9-1)(2)

Subtract 9-1

A(9) = -14+(8)(2)

Multiply 8*2

A(9) = -14+16

Add -14+16, which is the same as 16-14

**A(9) = 2**

The 9th term is 2.

A(9)= -14+(9-1)(2)

Subtract 9-1

A(9) = -14+(8)(2)

Multiply 8*2

A(9) = -14+16

Add -14+16, which is the same as 16-14

The 9th term is 2.

A(9) = -14 + (9-1)(2)

A(9) = -14 + (8)(2)

A(9) = -14 + 16

A(9) = 16 - 14

**A(9) = 2**

A(9) = -14 + (8)(2)

A(9) = -14 + 16

A(9) = 16 - 14

For this case, what you must do is place both numbers in a number line.

The largest number will be the number that is located farthest from the number 0.

We observe that the number that is furthest from zero is 5/8.

Therefore, it is fulfilled:

**Answer: **

**See attached image to see the numeric line.**

Place both numbers on the number line. The numbers are, in this order, 0, 1/8, 1/4, 3/8, 1/2, 5/8, 3/4, 7/8 and 1. You see, 5/8 comes after 3/8, so 5/8 is greater.